Predictors of short stature in Israeli children aged 6–7 years: a retrospective cohort study - Naama Fisch-Shvalb; Michal Yackobovitch-Gavan; Naomi Fliss-Isakov; Yair Morali; Nati Brooks; Moran Blaychfeld-Magnazi; Deena Rachel Zimmerman; Liora Lazar; Moshe Phillip; Ronit Endevelt (Israel Journal of Health Policy Research)
Abstract There are differences in the rates of short stature (WHO height-z score < -2SD) between the various sectors in Israeli children aged 6–7 years, with higher rates in the ultraorthodox Jewish population. We aimed to: (a) Compare the anthropometric data at 0–2 years of age and the obstetric and demographic data of children with short stature at 6–7 years of age with those of children with normal height. (b) Assess risk factors for short stature at the age of 6–7 years. (c) Evaluate the impact of clinical and socioeconomic factors on linear growth from birth to the age of 6–7 years. This was a retrospective cohort study. Anonymized anthropometric data measured at the first grade of school during 2015–2019 were collected from the Ministry of Health records. The participants were stratified into sectors according to the affiliation of their school. Retrospective growth and sociodemographic data were extracted for each child from the national birth registry and Maternal Child Health Clinics files. The cohort included 368,088 children, with a median age of 6.7 years (IQR 6.3,7.0). Short stature was more prevalent in ultraorthodox Jewish boys (3.8%) and girls (3.2%), and least prevalent in Arab boys (0.8%) and girls (0.7%) compared with all other sectors (P < 0.001). The rate of stunting in Bedouin children was similar to that in the general population (1.6%). In a logistic regression model, the variables that predicted short stature at the age of 6–7 years were female sex, longer gestation, lower height z-score at 2 months of age, birth weight < 90th percentile, being in the ultraorthodox Jewish sector, and a smaller change in height z-score until 2 years of age. Growth gaps between different sectors of school-aged Israeli children emerge during the first 2 years of life. The most vulnerable population for stunting is the ultraorthodox population. Public health services, including Maternal Child Health clinics and primary caregivers, should prioritize this group and closely monitor for growth faltering during the first and second years of life.